Monte Carlo model for the study of percolation thresholds in composites filled with circular conductive nano-disks - Oskouyi, Amirhossein Biabangard; Mertiny, Pierre (Procedia engineering, 2011)
The subject of the study described in this paper is the percolation threshold of composites with conductive nano-scale fillers. Specifically, a three-dimensional continuous Monte Carlo algorithm was developed to determine the percolation threshold of polymers filled with two-dimensional conductive circular nano-disks. The Monte Carlo simulation provides the threshold value of the filler loading when at least one percolation network is formed. A scaling study was carried out to determine the minimum dimension of the representative unit volume that ensures a percolation threshold that is independent of the unit cell size. The effect of the aspect ratio of the nano-particles and the tunneling distance on the percolation threshold was investigated employing the developed model. © 2011 Published by Elsevier Ltd. Selection and peer-review under responsibility of ICM11